LINGUOPRAGMATIC COMPONENTS OF TEXTS OF FOLK POETIC DISCOURSE (BASED ON TEXTS OF WORLD FOLK CONSPIRACIES) - Mukhamedova Shakhlo Muhammadalievna (International Engineering Journal For Research & Development, 2023)
Problems of linguopragmatic analysis of folklore text are of great importance for modern linguistics. The genre of folk conspiracy, despite numerous studies in the field of philology, is the least studied from this point of view. The purpose of this study is to study such linguopragmatic components of a folk poetic text as intention and opposition “addresser - addressee”. Discourse analysis of the material from the texts of folk spells made it possible to trace the peculiarities of changes in intention at the level of genre and thematic blocks of spells, as well as to establish the relationship between macro- and micro-intentions with spell formulas of various types. As a result, it was established that intention is revealed in a folk poetic text as a gradation of interacting components of a speech act. It has been revealed that the functions of the sender and addressee of the spell formula are determined by illocution. The results obtained contribute to the development of functional linguistics.